Piso-hamate hiatus syndrome in a patient with Riche-Cannieu anastomosis. (20th March 2013) - Rovers, Jörgen M P; Brekelmans, Geert J F; Visser, Leo H
Abstract : Various nerve anastomoses and anatomic variants in the nervous system have been described. It is important to be familiar with these anastomoses because they can mimic several clinical conditions, possibly leading to misdiagnosis. We report the case of a patient who experienced progressive loss of strength in his left hand without sensory complaints. On neurological examination atrophy was seen in the thenar and first dorsal interosseous muscles of the left hand. Serial electrophysiological studies ruled out motor neuron disease. Electromyography and nerve conduction studies revealed a Riche-Cannieu anastomosis in the left hand. In combination with piso-hamate hiatus syndrome, this anastomosis explained the clinical condition of the patient. It is important to be aware of this anastomosis and this syndrome because it can mimic motor neuron disease.